Principal Leadership Competencies for Educational Quality Improvement: A Qualitative Study - Masdar Limbong; Mansur Keling (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to determine the effectiveness of school principals’ leadership competencies in improving the quality of education. This study employs a descriptive qualitative approach. Data collection in this study includes: observation, interviews, documentation, and data triangulation. The results of the study indicate that 1) the leadership competencies of the principal at MAN 1 Medan already cover the aspects of personality, managerial skills, supervision, and social skills quite well. Although there are still some areas that need improvement, such as time management and program optimization, the leadership style implemented has generally been able to create a conducive work environment that supports the improvement of educational quality; 2) The principal’s competencies at MAN 1 Medan also demonstrate good performance, thereby contributing to the improvement of the educational quality of the institution. This is evident in several aspects, such as the teachers’ good performance, which is characterized by enthusiasm and discipline; improved student achievements; well-managed teacher administration; and the opportunities and support provided by the Principal to enhance their professionalism.